Abstracts from the 4th Grazer Risk Day: Patient Safety in Routine. Issue 1 (August 2016) - Hoffmann, Magdalena; Holl, Anna; Burgsteiner, Harald; Pieber, Thomas; Eller, Philipp; Amrein, Karin; Sendlhofer, Gerald; Leitgeb, Karina; Gombotz, Veronika; Tiefenbacher, Peter; Kamolz, Lars-Peter; Sendlhofer, Gerald; et al.
Table of contents A1 Meet the needs: Important questions for ICU relatives Magdalena M. Hoffmann1, 2, Anna K. Holl3, Harald Burgsteiner4, Thomas Pieber1, 5, Philipp Eller6, Karin Amrein1 A2 Daily use of the Surgical Safety Checklist: results of a real-time audit Gerald Sendlhofer1, 2, 3, Karina Leitgeb1, Veronika Gombotz1, Peter Tiefenbacher1, Lars-Peter Kamolz2, 3 A3 Best-practice projects concerning patient safety in Austria Gerald Sendlhofer1, 2, 3, 4, , Karina Leitgeb1, 4, Magdalena Hoffmann1, 4, Sabine Papst1, 4, Susanne Gasteiner1, 4, Lars Peter Kamolz2, 3, 4 A4 Comprehensive Cancer Center Graz: evaluation of availability of mandatory healthcare professionals in tumorboards Peter Tiefenbacher1, 2, Yvonne Müller1, 2, Gerald Sendlhofer1, 2, 3, 4 A5 Comprehensive Cancer Center Graz: protocol to evaluate communication and recommendation finding in tumorboards Marlies Hart1, Peter Tiefenbacher1, 2, Yvonne Müller1, 2, Gerald Sendlhofer1, 2, 3, 4 A6 Generating a new insulin prescription chart at a university hospital Julia Kopanz1, Katharina M. Neubauer1, Gerald Sendlhofer2, 3, 4, Barbara Semlitsch1, Andres Pak5, Gerald Cuder1, Thomas R. Pieber1, Johannes Plank6 A7 The Speech and Language Therapy teaching practice at the Institute for Speech and Language Therapy at FH JOANNEUM in Graz Annemarie Schinko1, Angelika Rother1 A8 Development and implementation of a progress test in undergraduate dental education: a prospective Austrian pilot project Barbara Kirnbauer1, Petra Rugani1, Norbert Jakse1, Johannes Bernhardt-Melischnig2, Rudolf Egger3 A9 What they need and what they get: protocol to identify the needs of information of patients and what they receive so far Magdalena M. Hoffmann1, 2, Karina Leitgeb1, 3, Esther Trampusch4, 5, Angelika Hofer4, Regina Riedl6, Karin Amrein2, Christa Tax7, Gernot Brunner7, Gerald Sendlhofer, 1, 3, 8 A 10 Medication-related problems resolved and money saved: results of a clinical pharmacy service evaluation in the surgical setting Emilie Tudela-Lopez1, Petra Pölzleitner1, Klara Jadrna1, Christina Labut1, Maria Kundracikova1, Helga Fend1, Gunar Stemer1 A 11 Intercultural communication management in radiology Jutta Maria Lorenz1 A 12 Spotlight on data quality: comparison of data input by physicians vs. non-physicians in the German Resuscitation Registry Gerhard Prause1, Paul Zajic1, Philipp Zoidl1, Geza Gemes1 A 13 MRSA prevalence and eradication with octenidine Gerald Pichler1, Christian Pux1, Rita Babeluk2, Brigitte Hermann3, Eric Stoiser3, Antonella De Campo4, Andrea Grisold5, Ines Zollner-Schwetz6, Robert Krause6, Walter Schippinger4 A 14 QUIPS: a pain registry with impact in science and daily routine work Alexander Avian1, 2, Brigitte Messerer3, Claudia Weinmann2, Winfried Meißner2 A 15 Patient empowerment for the youngest Karina Leitgeb1, Magdalena Hoffmann1, Gerald Sendlhofer1, 2, 3 A 16 Development of a pocket guide for parenteral nutrition in hospitalized adults Anna Maria Eisenberger1, Siegrid Fuchs2 A 17 Safety and efficacy of a clinical decision support system for blood glucose management in patients with diabetes mellitus type 2 at a plastic-surgical ward Alexandru-C. Tuca1, Katharina M. Neubauer2, Julia K. Mader2, Felix Aberer2, David B. Lumenta1, Birgit Bauer1, Klaus Donsa3, Thomas Augustin3, Bernhard Höll3, Lukas Schaupp2, Peter Beck4, Johannes Plank2, Thomas R. Pieber2, 3, Lars-P. Kamolz1, 5 A 18 Urban dwellers show higher readiness in participating actively in the shaping of the healthcare system in Austria Christian Smolle1, Frederike Reischies2, Gudrun Pregartner3, Daryousch Parvizi2, Gerald Sendlhofer1, 4, Lars-Peter Kamolz1, 4